Association of High Serum Uric Acid and Increased Arterial Stiffness is Dependent on Cardiovascular Risk Factors in Female Population - Yuan, Yin; Huang, Feng; Lin, Fan; Lin, Min; Zhu, Pengli (Hormone and Metabolic Research, 2019)
An elevated serum uric acid (SUA) level is closely associated with increased arterial stiffness. However, whether this association is independent of conventional cardiovascular risk factors is controversial. This study aimed to investigate whether SUA is independently associated with arterial stiffness as assessed by Brachial-ankle pulse wave velocity (baPWV), and to what extent this association is dependent on cardiovascular risk factors. Increased arterial stiffness was defined as baPWV>1 400 cm/s. Cardiovascular risk factors were defined as hypertension, diabetes, dyslipidaemia, and a BMI≥24.0 kg/m2. A total of 3 342 subjects (1 334 men and 2008 women, mean age 53.79±13.18 years) were included. SUA levels exhibited a graded elevation with an increasing number of cardiovascular risk factors. In female subjects with more than two cardiovascular risk factors, compared with the first quartile of SUA, higher SUA quartiles were associated with a higher probability of increased baPWV (OR=1.500, 1.478, 1.774 for SUA Q2–Q4). In further stratified association analysis, compared with Q1, SUA quartiles showed a graded association with increased baPWV in subjects with TC≥5.2 mmol/l (OR=1.758, 1.942, 2.354 for Q2, Q3, and Q4 respectively), LDL-C≥3.3 mmol/l (OR=1.510, 2.255 for Q3 and Q4) and FBG≥7.0 mmol/l (OR=1.516, 1.748 for Q3 and Q4). In the Chinese coastal female population, the association of high SUA and increased arterial stiffness is dependent on the coexistence of at least one cardiovascular risk factor, especially hypercholesterolemia.
Keywords: arterial stiffness; uric acid; cardiovascular risk factors